(untitled) (Bangladesh Journal of Psychiatry, 2018)
Mental health problems are often unrecognized and neglected by patients, their relatives and by the society. The objective of the study was to find out the pattern of psychiatric morbidity of the patients attending at the psychiatry outpatient department. This was a cross sectional study carried out in the department of Psychiatry at North Bengal Medical College Hospital (NBMCH), Sirajganj from August, 2015 to July, 2017. For this purpose, 918 respondents attending in psychiatry outpatient department of NBMCH were enrolled in the study by using convenient sampling technique. The results showed that majority (26.3%) were from the age group of 31-40 years with female preponderance (58.7%). Among them 71.8% were married and 71.1% came from rural background. Maximum respondent’s (56.3%) monthly family income was in between 15,000-30,000 BDT. The most common psychiatric morbidity among the respondents was major depressive disorder (38.6%) followed by anxiety disorsers (25.8%). Most (85.1%) of the respondents were referred either by themselves or by their family members, friends or by relatives. The rest (14.9%) were referred by general physicians and specialists of different disciplines. The result of this study may help in the planning for better mental health service in private medical college hospitals. Bang J Psychiatry June 2016; 30(1): 10-13